Re-creation of heritage: German experience of the XXI century - Nashchokina, Maria (project baikal, 2024)
The article presents an analysis of the works on reconstruction and recreation of the historical environment in Dresden and Frankfurt am Main during three decades. The peculiarity of the accomplished works is the attention to the lost urban environment, which was recreated on the basis of available archival and visual sources and on the surviving project documentation. Both examples are a clear illustration of the principles that should guide the reconstruction and return of the lost artistic quality to cities. These examples are important for our country, which lost a significant part of its historical, architectural and artistic heritage during the revolutions, wars and political cataclysms of the 20th century.
Keywords: reconstruction of pre-war ensembles in Germany; restoration of the centres of Dresden and Frankfurt am Main in the 21st century; combination of restoration and reconstruction methods; image-based reconstruction of lost buildings